STATE POLICY AS TO DEVELOPMENT STRATEGY OF URBANIZED TERRITORIES OF SMALL HISTORICAL TOWNS - Kravchenko S.G. (Pressing Problems of Public Administration, 2015)
The condition of the urbanized territories of small historical towns, and strategic vision of the role of sights of the national value in forming the urban environment have been analyzed. The specificity of the sights’ impact on the urbanized territories development is discussed. The influence of the state policy on the strategy of small historic towns’ development has been researched. The ways are suggested to preserve and maintain the sights for future use, as well as the main lines of further development of territories adjacent to or located within the zones of historical habitats are outlined.